Menakar Potensi Sosiologi Hukum sebagai Pendekatan Perdamaian: Pembacaan dari Perspektif Strukturasi Giddens - Harnadi, Dodik (Legal Studies Journal, 2021)
Positivistic legal approach still become dominant paradigm in the process of law enforcement. The dominance of the paradigm is also seen in the conflict resolution and peacebuilding process. Positive law is considered as the most effective instrument in overcoming conflict and tension. Unfortunately, its repressive nature making this approach also full of criticism.Such as its disregard of for the local norms as the living laws in society. This study of sociology of law as an approach in the peace process is aimed to fill the gap. Compared to the positivistic paradigm, the sociology of law is lack of popularity. The level of jurist acceptance of the sociology of law was also same. Along with the many criticism of the positivistic paradigm as it often gave rise to the gap between ideality of positive law and living law,  the popularity of sociology of law also began to rise. However, in the sense of peacebuilding, the sociological approach of law remains a novelty. This literature study analysed conceptually on how the sociology of law is applied to the local based peacebuilding. The strong emphasis on the local habit and norm as living law become a meeting point between the sociology of law and local based peacebuilding. In addition, to explain how local individuals act as an empowered agent in accordance with living law, this study utilized Giddens' theory of Structuration.Keywords: Living law, Peacebuilding, Local, Agent.